Tribological evaluation of N-phenylformamidino-N′-alkylthiocarbamides and their Mo-S complexes as EP lubricant additives - Tripathi A.K.; Bhattacharya A.; Singh R.; Prasad N.; Verma V.K. (My University, 2025)
The tribological properties of 0.5% solutions of N-phenylformamidino-N′-alkylthio-carbamides and their Mo-S complexes, i.e., μ-hydroxo-μ-(N-phenylformamidino-N′-alkylthiocarbamido)-bis- (dioxohydroxo molybdenum VI) in paraffin oil were evaluated in a four-ball test. In particular, μ-hydroxo-μ-(N-phenylformamidino-N′-ethylthiocarbamido)-bis- [dioxohydroxo molybdenum VI] was found to exhibit an appreciable increase in the load carrying capacity and values of flash temperature parameter, load wear index and pressure wear index and a decrease in the values of coefficient of friction. However, the Mo-S additives did not markedly improve anti-wear characteristics in the wear tests. A comparative EP evaluation of μ-hydroxo-μ-(N-phenylformamidino-N′-ethylthiocarbamido)-bis- (dioxohydroxo molybdenum VI) using steel balls of different compositions, indicated its suitability of replacing alloy steel balls with cheaper carbon steel balls. The topography of the wear scars on the used steel ball specimen was studied by SEM.